White death - Vicary, Tim 1949- (Oxford ; New York : Oxford University Press, 2008)
Sarah Harland is nineteen, and she is in prison. At the airport, they find heroin in her bag. So, now she is waiting to go to court. If the court decides that it was her heroin, then she must die. She says she did not do it. But if she did not, who did? Only two people can help Sarah: her mother, and an old boyfriend who does not love her now. Can they work together? Can they find the real criminal before it is too late?
G
"First published in Oxford Bookworms, 1989"--T.p. verso.
310
G
Keywords: Readers (Adult); English language -- Textbooks for foreign speakers; Reading comprehension -- Problems, exercises, etc; Teenage girls -- Fiction; Drug traffic -- Fiction; Suspense fiction